G351(P) Evaluation of treatment and outcomes in paediatric patients with whooping cough (bordatella pertussis) at a hospital trust from 2012–2017. (May 2019) - Bodimeade, CG; Radcliffe, R; Perera, N; Pearce, D
Abstract : This retrospective study investigates the adherence to local guidelines during the treatment of paediatric patients with pertussis and follows their clinical outcome at a Hospital Trust between 1stJanuary 2012 and 31stDecember 2017. Forty-four Bordatella pertussis patients were identified through clinical coding or microbiological confirmation. Five patients were excluded due to insufficient clinical data, duplication or community treatment. The remaining thirty-nine patients were evaluated by systematically reviewing their clinical notes; recording whether the patients were correctly investigated, treated and notified to Public Health England (PHE), as well as the patient's clinical outcome. This information was corroborated with the PHE records of pertussis notifications over the same period. Results demonstrated that 31 (84%, n=37) patients were correctly investigated with either pernasal swabs, nasopharyngeal aspirates (NPA) or serological testing. 17 (46%, n=37) patients were treated correctly according to local guidelines. The remainder were non-adherent to guidelines generally due to choice, timing or duration of antibiotic. 8 (21%, n=39) patients had notification to PHE recorded in their clinical notes, well below the 23 (53%, n=43) cases that PHE were informed of according to their records. 11 (28%, n=39) patients were admitted to Paediatric Intensive Care Unit (PICU), 5 (13%, n=39) patients received Extracorporeal Membrane Oxygenation (ECMO) and 6 (15%, n=39) patients died. Mortality rate was 45% (n=11) for those admitted to PICU and 80% (n=5) for those who received ECMO. Further analysis showed a statistically significant increased average length of time between admission and diagnosis for those that died compared to those that survived (p = 0.03 ). These findings show considerable room for improvement in the optimal treatment of pertussis patients and should inform future pertussis guidelines. In particular, greater emphasis should be put on patients with symptoms lasting >3 weeks, who were responsible for the majority of incorrect investigations and treatments. Furthermore, evidence suggests faster diagnosis of pertussis patients may lead to improved clinical outcome.